PELATIHAN JARINGAN KOMPUTER MENGGUNAKAN MODUL SURVEILLANCE CAMERA DI SMK NEGERI 1 TEJAKULA - Santo Gitakarma, Made; Indrawan, Gede; Sutaya, I Wayan (Universitas Pendidikan Ganesha, 2018)
The security problem is an important issue in every aspect of human life. Surveillance Camera or monitoring camera is one of sollution for reliability and flexibility camera, even able to be accessed via the Internet. SMK Negeri 1 Tejakula not yet using the security system with CCTV or Surveillance Camera. The module donated to P2M was designed can be connected to a computer via cable, wireless and accessible via smartphone. This P2M is expected to increase student interest in computer networks (TKJ) and to provide a security system solutions for the convenience at SMK Negeri 1 Tejakula. The training was well implemented and successfully aroused students interest in the field of computer networks and motivated teachers to provide practical materials using the modules provided. Overall mastery of basic competencies in this training is 80.11 which exceeds 70% of KK or has succeeded in accordance with expectations